Comparing tacrolimus level monitoring in peripheral blood mononuclear cells and whole blood within one year after kidney transplantation: a single-center, prospective, observational study - You, Jia; Chen, Rui; Chai, Yuhui; Wang, Xue; Xie, Wenmin; Yang, Yunyun; Zheng, Kaile; Chen, Lizhi; Wang, Zhuo; Wang, Xuebin (Frontiers in Pharmacology, 2025)
BackgroundTacrolimus, a key immunosuppressant for kidney transplant recipients, is traditionally monitored through whole-blood trough concentrations. However, this approach may not accurately reflect lymphocyte tacrolimus levels, limiting its predictive value for allograft function and rejection. Monitoring tacrolimus levels in peripheral blood mononuclear cells (PBMCs) offers a potentially more precise alternative, though its clinical value remains unclear. This study aimed to compare tacrolimus intra-patient variablity (IPV), allograft function, and de novo donor-specific anti-HLA antibody (dnDSA) status between PBMC-based and whole-blood tacrolimus monitoring methods to assess whether PBMC monitoring provides greater clinical utility.MethodsThis single-center, prospective, observational, non-interventional study enrolled kidney transplant recipients between November 2021 and February 2023. At six follow-up time points after transplantation (Day 7, Day 14, Month 1, Month 3, Month 6, and Month 12), tacrolimus levels in PBMCs and whole blood were measured, and IPVs in both matrices were calculated. Pearson’s or Spearman’s correlation analyses were used to evaluate (1) the relationship between tacrolimus levels in PBMCs and whole blood, (2) their association with allograft function, and (3) the correlation of tacrolimus IPV with allograft function and dnDSA status.ResultsA total of 60 kidney transplant recipients were included. Within 1-year post-transplantation, the PBMC tacrolimus levels were 3.6% of whole-blood levels (P < 0.01). Tacrolimus levels in PBMCs and whole blood showed positive correlations across six-time points, with statistically significant correlations on Day 7, Day 14, Month 3, and Month 6 (P < 0.05). Notably, PBMC tacrolimus levels demonstrated stronger associations with creatinine clearance and estimated glomerular filtration rate at multiple timepoints compared to whole-blood measurements. Patients with dnDSA exhibited significantly higher IPV in PBMC tacrolimus levels than dnDSA-negative counterparts (P < 0.05), a pattern not observed in whole-blood analysis.ConclusionMonitoring tacrolimus levels and IPVs in PBMCs provides greater insight into allograft function and dnDSA status than whole-blood measurements. These findings suggest that PBMC-based tacrolimus monitoring may enhance clinical value in managing kidney transplant recipients.